Aberrant Metabolism as Inductor of Epigenetic Changes in Breast Cancer: Therapeutic Opportunities - Coronel-Hernández, Jossimar; Pérez-Yépez, Eloy Andrés; Delgado-Waldo, Izamary; Contreras-Romero, Carlos; Jacobo-Herrera, Nadia; Cantú-De León, David; Pérez-Plasencia, Carlos (Frontiers in Oncology, 2021)
Aberrant metabolism is arising interest in the scientific community not only because of the role it plays in the development and establishment of the tumor mass but also the possibility of drug poisoning of key enzymes overexpressed in tumor cells. Moreover, tumor metabolism provides key molecules to maintain the epigenetic changes that are also an undisputed characteristic of each tumor type. This metabolic change includes the Warburg effect and alterations in key pathways involved in glutaminolysis, pentose phosphate, and unsaturated fatty acid biosynthesis. Modifications in all these pathways have consequences that impact genetics and epigenetics processes such as DNA methylation patterns, histone post-translational modifications, triggering oncogenes activation, and loss in tumor suppressor gene expression to lead the tumor establishment. In this review, we describe the metabolic rearrangement and its association with epigenetic regulation in breast cancer, as well as its implication in biological processes involved in cancer progression. A better understanding of these processes could help to find new targets for the diagnosis, prognosis, and treatment of this human health problem.